Voz e trabalho: estudo dos condicionantes das mudanças a partir do discurso de docentes - Biserra, Mariana Pelegrini (2013)
Objective: Analyzing as to demonstration of worsening or improvement about work ability, the conditioning aspects of changing regarding between work and voice, in the professors speech from elementary and middle public school in São Paulo. Method: in the first stage, 85 teachers have been invited that, in the previous researching, they have demonstrated vocal and laryngeal alteration, as the low and moderated index about the answering Work Ability Index (WAI). Among them, 52 teachers have accepted to answer the same instrument again. After the comparison analyzing of data about WAI, the teachers have showed a great difference as improvement (28 people) as worsening (24 people) regarding the first application, six in each modality, they had been selected and arranged to attend a focus group meeting, compound two groups: one, with bad results (group A) and, the other, with good results (group B), that they had been invited to discuss which aspects could explain the improvement or worsening of results from WAI. The reports have been transcribed and analyzed qualitatively for category in two thematic axes (voice and work), according to the recurrence enunciated. Results: Concerning the voice, although both groups, all the teachers have been referred improvement in the voice quality and changing vocal habits, after doing the treatment, half of the teachers who were heard, they showed vocal complaint, associated to the others factors different those brought them the job previously. Further as regards the aspects of health and voice, in the group B, there has been a reference the fact to be multiplied as far as voice care; while group A, there has been a standout in the reports about musculoskeletal disorders and intense psychological suffering. Regarding the work, both groups reported that they have been living with the violence, indiscipline, inappropriate physical environment, lack of support and partnership with the students families. However, the difference among groups were about the difficult relationship, lack of self-reliance at work and lack of support from co-workers and the school authorities, that showed in a way unanimous and very intense in the group A; while group B the teachers reported to have self-reliance, exist a support from co-workers and school authorities, in addition to personal transformation who lead to appropriate and self-reliance about caring themselves. Conclusion: It was possible to record that group A had a poor condition (not just with the voice) and with more necessity to talk about the problems at work. And group B showed more strength to face the difficulties at work, in fact, with creative proposals. In favor of this group have been also recorded better relations at work as for social support and self-reliance